Variabilidade espacial de atributos físicos em um cambissolo háplico, sob diferentes usos na região sul do Amazonas - de Oliveira, Ivanildo Amorim [UNESP]; Campos, Milton César Costa; Soares, Marcelo Dayron Rodrigues; de Aquino, Renato Eleotério [UNESP]; Marques Júnior, José [UNESP]; do Nascimento, Ediana Pereira (FapUNIFESP (SciELO), 2013)
Considering the importance of knowledge of the spatial distribution of soil properties, the purpose of this study was to evaluate the spatial variability of physical properties in a Cambisolunder different land uses in the southern Amazon region. The study was conducted on three farms with cassava, sugarcane, and agroforestry, in the region of Humaitá, in the south of the State of Amazonas. In these areas, 70 x 70 m grids were established, with a regular spacing of 10 x 10 m and a total of 64 points, where soils were sampled at 0.0-0.10 m depth. Texture (sand, silt, and clay), macroporosity, microporosity, total porosity, bulk density, and aggregate stabilitywere determined. The data were analyzed using descriptive statistics and geostatistics. It was found that the propertiesvaried spatially and that the range of these variations between land uses was different, with the highest variability for the sugarcane management.
Spatial variability of physical properties in a cambisol under different land uses in the southern Amazon region
Keywords: Geostatistics; Soil management; Soil properties